Effects of soils flooding.Influence of on pH, oxidation-reduction potencial and soil phosphorus availability - Moraes, José Francisco Valente (Pesquisa Agropecuaria Brasileira, 2014)
Four soils and four levels of phosphorus (0, 40, 80 and 120 kg/ha) have been used with the objective of studying the influence of waterlogging on pH, redox potential and phosphorus availability. The pH, the Eh, the phosphorus of the soil solution and phosphorus extracted from soil by an anion exchange resin were determined every 7th day during the flooding period. The pH of the acid soils increased and the pH of the alkaline soil decreased after inundation. In both cases the final values were between 6.5 and 7.0. The redox potentials of the soils changed remarkably after waterlogging. The Eh of the soils decreased rapidly for the 5 first weeks of submergence followed by a slow decrease between the 5th and 7th weeks, at which time Eh values became stable, between - 200 and - 300 mV. Phosphorus applied to soil as a fertilizer was fixed at the beginning of the flooding. Availability increased only after pH and Eh changes had taken place. Both extracted and soil solution phosphorus increased with time of inundation. Correlation coeficients between these two forms of phosphorus were 0.91, 0.85, 0.90 and 0.88 respectively for the soils La Granja loam, Mesillas clay, Hogamacho clay and Piedras Negras clay. It was observed that soil temperature influenced the velocity of changes on pH, Eh and phosphorus availability.